Persepsi Tentang Mata Pelajaran IPS bagi Peserta Didik Berprestasi Rendah (Kasus pada Kelas VII di SMP Muhammadiyah Palangka Raya) - Sinta Kumala Dewi; Diplan Diplan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This researcher aims to find out the learning activities of students and find out the perceptions of students about social studies subjects. This study used a descriptive qualitative research approach, which was the subject of this study were eight students at the Muhammadiyah Middle School in Palangka Raya. Data collection techniques using observation sheets, interviews, and documentation. The data analysis technique used is qualitative descriptive analysis. The results of the study found that students with low achievement had negative perceptions of social studies subjects. This is illustrated by The way teachers teach who always asks students to record too much and teachers are less able to approach the students with low achievement, and Schedule of social studies subjects that are available during the day so that students feel lazy to take social studies subjects